BENCHMARKING: INTERNATIONALIZATION STRATEGY FOR SMALL AND MEDIUM-SIZED COCOA DERIVATIVE COMPANIES IN PIÑAS - Bueno Fajardo, Tatiana; Solórzano Solórzano, Sandra; Carmenate Fuentes, Luis (mktDESCUBRE; Vol 1 No 3 (2020): Special Edition 1st International Marketing Congress, 2020)
Benchmarking as an internationalization strategy allows you to have references, models and best practices that companies develop and then make a comparison of what is done and what is not. This serves to learn the best of the competition. The theoretical conceptual foundations of this tool were analyzed to identify the strategies that three large Ecuadorian companies have internationalized: Pacari, Republic of Cocoa and Chchukululu. These strategies were related to the Chocodamas Association, dedicated to the elaboration of cocoa derivatives, located in the Piñas canton. Theoretical and empirical methods were used to gather information about small and medium enterprises. The research results describe the strategies used by the three companies and the relevance of their application in Chocodamas to obtain better performance and sustainable competitive advantages that give way to internationalization.